High performance multiply-accumulate unit for residue number system DSP core - Pretthy, A. P. (2008)
High speed computing continues to inspire the researchers, especially in the more demanding areas like digital signal processing and multimedia applications. In this regard multiplier designs and multiplier-accumulator units (MAC) have long been a topic of interest to the digital community due to their extensive use in almost every digital design. Many innovative techniques have been used in the past for the design of multipliers by making use of the number theoretical properties of finite fields. Even though a few of these designs were based on the structure of polynomial rings, the properties of finite integer rings have not been exploited to their full potential so far.